A hidden history of youth development in South Africa : learning in transition - Perrow, Margaret (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Drawing on two decades of interviews and ethnographic fieldwork (1998 to 2018), this book presents a unique and multi-faceted history youth development in South Africa through the lens of a South African NGO prominent in youth development from the mid-1980s until 2008. The book weaves history, ethnography, and discourse analysis to contextualize the Joint Enrichment Project (JEP) in the politics and history of South African education. It examines JEP's role leading up to and during South Africa's transition to democracy, its work and influence in post-apartheid South Africa, and the continued relevance of its legacy to contemporary initiatives seeking to address youth development and social justice. While JEP repeatedly repositioned itself as an organization, from fighting the effects of apartheid on young people to becoming a potential partner with the new ANC-led government, its most significant role may have been to reposition people. After tracing JEP's twenty-year history, the book focuses on the participants in a 1998 Youth Work Scheme, exploring their learning experiences and the program's immediate impact on their lives. It then revisits these participants twenty years later, in 2018, analyzing their life trajectories after JEP and comparing them with the life trajectories of former JEP staff over the same period-shedding light on broader patterns of socio-economic reproduction and change in the country. The book concludes with a discussion of a perennial paradox facing youth-development institutions. This book will be of great interest to academics, researchers and post-graduate students in the fields of education, international development, anthropology, and African studies"--
Preface. What would our ancestors say to each other? -- Acronyms -- Introduction. "Siyi youth endala" (We are old youth) -- Learning on contested grounds: Education, resistance, and youth development -- Shifting discourses, shifting identities: A history of the Joint Enrichment Project -- "I better do something": The Youth Work Scheme and its participants -- "Gaining skills and moving around": Repositioning at an orientation and a worksite -- "I can be somebody": Negotiating identity in a deployment workshop -- "A time-being thing": Participants after the Youth Work Scheme -- "Too slow, too fast": Staff after the Joint Enrichment Project -- "Something that can't be lost": The Joint Enrichment Project's legacy -- "In the next future": Reflections on NGOs in South Africa.
OCLC-licensed vendor bibliographic record.
Keywords: Joint Enrichment Project (South Africa) -- History; Youth -- Services for -- South Africa; Youth development -- South Africa; Community education -- South Africa; EDUCATION / General